BI-GELS: A NOVEL MATERIAL FOR TRANSDERMAL DRUG DELIVERY - RAJESWARI, SARIPILLI; PULLABHATLA, RAJESWARI; SATYAVATHI, CHUKKA YERNI (Innovare Journal of Sciences, 2021)
Bi-gels semi solid formulation is combination of organogel and hydrogel with better application property such as pharmaceutical and cosmetics. The main objective of this review is specially focuses on application of bi-gels as drug delivery vehicles by transdermal route. It contains two different phases which are polar and nonpolar due to which, it possess some significant features such as ability to deliver the hydrophilic and hydrophobic drugs which also have improved permeability of drugs, better spreading ability, and water wash ability. Hence, bigels have both organogels and hydrogels they can enhanced hydration of stratum corneum and also had an ability to manipulate the drug release rate from the dosage from.